Immunotherapy as a way to increase the effectiveness of comprehensive treatment of pelvic inflammatory diseases - N.A. Urakova; T.V. Ipatova (LCC «Medicine-Inform», 2018)
Immunotherapy as a way to increase the effectiveness of comprehensive treatment of pelvic inflammatory diseases N.A. Urakova1, T.V. Ipatova2 1 Izhevsk State Medical Academy, Izhevsk, Russian Federation 2 Zavyalovskaya District Hospital, Zavyalovo, Russian Federation The problem of the prevalence of limited pelvic inflammatory diseases in women of childbearing age remains highly relevant. It has been established that pathogenic microorganisms play a central role in the etiology and pathogenesis of localized pelvic inflammatory diseases in women. An application of antimicrobial and anti-inflammatory drugs is often not sufficient to achieve a stable clinical effect. In recent years, it has been shown that the possibility of increasing the effectiveness of standard treatment is associated with the use of immunotherapy. Aminodihydrophthalasindione sodium refers to immunomodulators with anti-inflammatory action; proved its effectiveness in the treatment of various infectious and inflammatory diseases. Aim: to evaluate the effectiveness of a course of immunotherapy with aminodihydrophthalasindione sodium (Galavit®) when standard treatment of pelvic inflammatory diseases is included in women of childbearing age. Patients and Methods: an observational study was conducted with 140 women of childbearing age with localized pelvic inflammatory diseases. All patients received antimicrobial and eubiotic therapy; in the main group (n=70) Galavit® was prescribed. Clinical observations were made of the symptoms dynamics of genital organs inflammation before and after treatment (after 3 months) in the main and control group (n=70) with standard therapy. Results: it was shown that the course of Galavit® increases the effectiveness of comprehensive treatment of pelvic inflammatory diseases in women of reproductive age. It was revealed that the course of immunotherapy with Galavit® reduces pain in women with palpation, reduces purulent and mucous discharge, reduces dyspareunia, itching, and burning, which is statistically significant in a larger proportion of patients compared with the control group. Conclusion: comprehensive therapy with the application of Galavit® increases the effectiveness of treatment of pelvic inflammatory diseases in women. Key words: women, childbearing age, localized pelvic inflammatory diseases, pain, discharge, antibacterial therapy, immunotherapy, aminodihydrophthalasindione sodium, Galavit. For citation: Urakova N.A., Ipatova T.V. Immunotherapy as a way to increase the effectiveness of comprehensive treatment of pelvic inflammatory diseases. Russian Journal of Woman and Child Health. 2018;1(2):120-123.